ECONOMETRIC ASSESSMENT OF THE EFFICIENCY OF "ECONOMIC" DIRECTIONS IN THE MARKET OF EDUCATIONAL SERVICES (Marketing Journal, 2025)
33 In this study, the effectiveness of "Economics" areas in the educational services market is assessed based on modern econometric methods. The main variables in the work are the quality of personnel training, the position of graduates in the labor market, the level of their wages, and employment indicators. Using regression models built on panel data, the relationship between the quality of education and economic results is analyzed. The study considers important econometric problems such as statistical significance, multicollinearity, and autocorrelation. Based on the obtained results, scientifically based proposals aimed at increasing the effectiveness of economic education are being developed.
Keywords: econometric analysis; economic education; performance indicators; labor market; panel data; regression model; employment rate; education services market